K-MEANS ALGORITHM TO DETERMINE THE EFFECTIVENESS OF USING QUIZIZZ IN ENGLISH LANGUAGE LEARNING FOR STUDENTS - Moeh Zainal Khairul,; Hardianti Hafid , (English Language, Linguistics, and Culture International Journal, 2024)
Mastery of the English language in the era of globalization has become an essential skill required in various aspects of life. Challenges in the teaching and learning of English, such as limited learning resources and unengaging teaching methods, call for innovative solutions to enhance learning effectiveness. This research explores the use of Quizizz, a game-based learning platform, as an interactive learning medium in teaching English to students at SMP IT Al-Akhyar Makassar. This study aims to assess the effectiveness of implementing Quizizz in improving students' understanding of English by using the K-Means algorithm for analyzing students' learning performance data. The research method involves collecting students' grades before and after the implementation of Quizizz in English learning. The data were analyzed using the K-Means algorithm to classify students into clusters based on their improvement in understanding. The evaluation of the clustering model was conducted by comparing the average within-cluster distance and the average between-cluster distance to assess the cohesiveness and differentiation among clusters. The results show a significant improvement in students' understanding of English after the implementation of Quizizz, indicated by the shift of student allocation into clusters with higher criteria, namely excellent. The evaluation of the clustering model shows that the clusters were formed effectively, with strong internal cohesion and clear differentiation between clusters. This supports the claim that Quizizz helps people learn English better.